2015
DOI: 10.1007/s11012-015-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Regular and chaotic vibration in a piezoelectric energy harvester

Abstract: We examine regular and chaotic responses of a vibrational energy harvester composed of a vertical beam and a tip mass. The beam is excited horizontally by a harmonic inertial force while mechanical vibrational energy is converted to electrical power through a piezoelectric patch. The mechanical resonator can be described by single or double well potentials depending on the gravity force from the tip mass. By changing the tip mass we examine bifurcations from single well oscillations, to regular and chaotic vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…2, may present better power recovering performances, when compared to the linear counterparts. The richness of such devices dynamics, combined with the new available improvements in numerical simulation tools and computing resources, have been propelling a wide variety of analysis considering different devices layouts, as seen in [10,18,34,39] for composite and cantilever vibrating beams, or in [11,15,25,26] for inverse pendulum layouts and new designs as those discussed in [5,8,16,33,45].…”
Section: Introductionmentioning
confidence: 99%
“…2, may present better power recovering performances, when compared to the linear counterparts. The richness of such devices dynamics, combined with the new available improvements in numerical simulation tools and computing resources, have been propelling a wide variety of analysis considering different devices layouts, as seen in [10,18,34,39] for composite and cantilever vibrating beams, or in [11,15,25,26] for inverse pendulum layouts and new designs as those discussed in [5,8,16,33,45].…”
Section: Introductionmentioning
confidence: 99%
“…The vibration of the working parts, such as vibrating screen, detached roller and fan, need to be tested on the basis of the above analysis, and the larger vibration points of each part under different working conditions should be tested in detail. The test results show that the vibration of the transport trough and the threshing device mainly originates from the transmission shaft, while the vibration of the drum and the fan is mainly from the installation, and the vibration produced by itself is little (Litak et al, 2016). To sum up, the main vibration of the combine harvester comes from the cutting structure, the vibrating screen and the engine, moreover, the conveying tank, the threshing roller and the fan will also affect the vibration of the crawler-type combine harvester.…”
Section: Analysis For Vibration Source Of Crawler-type Combine Harvestermentioning
confidence: 99%
“…Among various proposals for energy harvesting, inverted pendulum systems have been tested [19][20][21][22]. On the other hand, studies on horizontal beams with amplitude limiters can be also found [23].…”
Section: Introductionmentioning
confidence: 99%